2019
DOI: 10.15353/cjds.v8i4.532
|View full text |Cite
|
Sign up to set email alerts
|

On Survival and Education: An Academic’s Perspective on Disability

Abstract: When illness and disability strike, it can seem as though one’s very being is threatened. We tend to consider illness a temporary situation, a phase, a phase that will be done with, sooner or later, and the victim of the attack will be rectified, and will survive it. But in chronic illness, there is a gap, a missing piece that cannot be found, despite all attempts. This is not necessarily a loss, as to claim that there is a loss falls into dangerous territory of positing a once complete or whole body and/or se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is common to find individuals with disabilities in the Arab gulf region employed in jobs where career progression is limited or altogether kept out of the workforce (Al Tarawneh 2016;Mansour 2009) and around the world (Loja et al 2013;Ozawa et al 2016;Yardimci and Bezmez 2018). It is reported that individuals with disabilities are faced with a double-edged sword; they not only face the barriers related to their own disabilities, but also the discriminatory disablement of society's understandings of disability (Azhar 2014;Alshammari 2019). In addition to these issues, Abusukkar (2019), Kadi (2018), and Morgan (2021) reported poor work environments and a lack of a clear reason around support for employment for individuals with disabilities.…”
Section: Employment Of Individuals With Disabilitiesmentioning
confidence: 99%
“…It is common to find individuals with disabilities in the Arab gulf region employed in jobs where career progression is limited or altogether kept out of the workforce (Al Tarawneh 2016;Mansour 2009) and around the world (Loja et al 2013;Ozawa et al 2016;Yardimci and Bezmez 2018). It is reported that individuals with disabilities are faced with a double-edged sword; they not only face the barriers related to their own disabilities, but also the discriminatory disablement of society's understandings of disability (Azhar 2014;Alshammari 2019). In addition to these issues, Abusukkar (2019), Kadi (2018), and Morgan (2021) reported poor work environments and a lack of a clear reason around support for employment for individuals with disabilities.…”
Section: Employment Of Individuals With Disabilitiesmentioning
confidence: 99%